The relationship between flow experience and teaching well-being of university music teachers: The sequential mediating effect of work passion and work engagement - Wang, Xiaoxiao (Frontiers in Psychology, 2022)
Objective The purpose of this study was to investigate the relationship between work passion and work engagement among university music teachers in flow experience and teaching well-being. Methods Three hundred forty-three university music teachers were tested by using the Flow State Scale, Teacher Well-Being Scale, Work Passion Scale, and Work Engagement Scale. Results University music teachers’ flow experience can predict teaching well-being (β = 0.248, p < 0.001). University music teachers’ flow experience has an indirect impact on teaching well-being through work passion (β = 0.257, p = 0.005), and university music teachers’ flow experience has an indirect impact on teaching well-being through work engagement (β = 0.144, p = 0.018). In addition, work passion and work engagement play a chain-mediating role between university music teachers’ flow experience and teaching well-being (β = 0.134, p = 0.001). Conclusion Work passion and work engagement play a sequential mediating role between university music teachers’ flow experience and teaching well-being.